Interaction between the Msh2 and Msh6 Nucleotide-binding Sites in the Saccharomyces cerevisiae Msh2-Msh6 Complex - Hargreaves, Victoria V. (American Society for Biochemistry and Molecular Biology, 2010)
Indirect evidence has suggested that the Msh2-Msh6 mispair-binding complex undergoes conformational changes upon binding of ATP and mispairs, resulting in the formation of Msh2-Msh6 sliding clamps and licensing the formation of Msh2-Msh6-Mlh1-Pms1 ternary complexes. Here, we have studied eight mutant Msh2-Msh6 complexes with defective responses to nucleotide binding and/or mispair binding and used them to study the conformational changes required for sliding clamp formation and ternary complex assembly. ATP binding to the Msh6 nucleotide-binding site results in a conformational change that allows binding of ATP to the Msh2 nucleotide-binding site, although ATP binding to the two nucleotide-binding sites appears to be uncoupled in some mutant complexes. The formation of Msh2-Msh6-Mlh1-Pms1 ternary complexes requires ATP binding to only the Msh6 nucleotide-binding site, whereas the formation of Msh2-Msh6 sliding clamps requires ATP binding to both the Msh2 and Msh6 nucleotide-binding sites. In addition, the properties of the different mutant complexes suggest that distinct conformational states mediated by communication between the Msh2 and Msh6 nucleotide-binding sites are required for the formation of ternary complexes and sliding clamps.